2018
DOI: 10.1039/c8ee00580j
|View full text |Cite
|
Sign up to set email alerts
|

Improving the stability and performance of perovskite solar cells via off-the-shelf post-device ligand treatment

Abstract: A simple off-the-shelf post-device ligand treatment is developed to simultaneously improve the performance and air stability of perovskite solar cells, as well as repair as-prepared ‘poor devices’ for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
132
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(141 citation statements)
references
References 54 publications
8
132
1
Order By: Relevance
“…The light intensity dependent J–V curves are shown in Figure S22b (Supporting Information) and the detailed photovoltaic parameters are summarized in Table S5 (Supporting Information). The almost unchanged V oc indicates that the trap‐related nonradiative recombination is effectively suppressed,41,50 which agrees well with the SCLC analysis presented in Figure 1. The slight PCE improvement is due to the low recombination under weak illumination 51.…”
Section: Resultssupporting
confidence: 88%
“…The light intensity dependent J–V curves are shown in Figure S22b (Supporting Information) and the detailed photovoltaic parameters are summarized in Table S5 (Supporting Information). The almost unchanged V oc indicates that the trap‐related nonradiative recombination is effectively suppressed,41,50 which agrees well with the SCLC analysis presented in Figure 1. The slight PCE improvement is due to the low recombination under weak illumination 51.…”
Section: Resultssupporting
confidence: 88%
“…These results indicate lower trap states of perovskite film due to the superior crystallization by introducing I 2 into PbI 2 precursor. Less trap states is believed to reduce the recombination and improve the extraction of carrier . To measure the trap‐state density in the perovskite film, we fabricated electron‐only devices (FTO/TiO 2 /CH 3 NH 3 PbI 3 /PCBM/Ag).…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that excessive additive addition causes a better crystallinity but also enables the formation of huge grain gaps, which deteriorates the resulting photovoltaic performances . To improve the quality of perovskite films, various effective post‐treatment methods have been reported such as vapor treatment, ligand‐assisted postdeposition, and vertical recrystallization …”
Section: Introductionmentioning
confidence: 99%